2014
DOI: 10.1158/1055-9965.epi-13-1180
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Prostate Cancer Genomic Alterations Predict Response to Brachytherapy Treatment

Abstract: Background This study aimed to evaluate the association of recurrent molecular alterations in prostate cancer, such as ERG rearrangements and phosphatase and tensin homolog gene (PTEN) deletions, with oncologic outcomes in patients with prostate cancer treated with brachytherapy. Methods Ninety-two men underwent I-125 brachytherapy with a 145 Gy delivered dose between 2000 and 2008. Pretreatment prostate biopsies were analyzed by immunohistochemistry (IHC) and FISH for ERG rearrangement and overexpression, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
2
16
1
Order By: Relevance
“…We are unable to differentiate whether the clonal heterogeneity we observe is a result of multiple different foci with distinct cells of origin or clones arising from the same cell in which these genomic aberrations have occurred stochastically. Although there is an association between ERG rearrangement and PTEN deletion (28, 29), here we identified a higher prevalence of loss of PTEN and NKX3.1 than reported previously. The detection of coexistent clones, each with a different ERG status, is in contrast to previous studies on metastases obtained at rapid autopsy or CTC data that reported 21q deletion in all CRPC tissue from the same patient (2, 30).…”
Section: Discussioncontrasting
confidence: 87%
“…We are unable to differentiate whether the clonal heterogeneity we observe is a result of multiple different foci with distinct cells of origin or clones arising from the same cell in which these genomic aberrations have occurred stochastically. Although there is an association between ERG rearrangement and PTEN deletion (28, 29), here we identified a higher prevalence of loss of PTEN and NKX3.1 than reported previously. The detection of coexistent clones, each with a different ERG status, is in contrast to previous studies on metastases obtained at rapid autopsy or CTC data that reported 21q deletion in all CRPC tissue from the same patient (2, 30).…”
Section: Discussioncontrasting
confidence: 87%
“…In a study of 262 patients [40], loss of PTEN protein expression by IHC was more strongly associated with biochemical recurrence among ERG-positive compared to ERG-negative tumors. Similar findings have been reported for a cohort of patients treated with brachytherapy [41]. Only one study has examined the interaction of PTEN and ERG and their association with PCa-specific mortality in a cohort of 308 patients managed conservatively [16].…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, this may be why PTEN loss was not significant in the final multivariate models for ERG-negative tumors, but was significant for ERG-positive tumors. In previous studies, only between five and 19 ERG-negative tumors with PTEN loss were available for follow-up [21,40,41], so the studies may also have been underpowered for observation of an association with outcome in this subgroup. By contrast, the largest FISH-based study that found no effect of ERG status on the association of PTEN loss with progression examined 97 and 356 ERG-negative PTEN-loss tumors in the original and expanded series [17,39].…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains unclear why this enrichment of PTEN loss occurs among ERG‐positive acinar tumors in humans, genetically engineered mouse models have suggested these two genetic alterations may have synergistic effects on tumor cell growth, migration and androgen signaling, leading to selection for ERG‐positive PTEN‐negative tumor clones . However, human studies examining the interaction between PTEN loss and ERG expression for disease outcomes have been mixed . This raises the possibility that ERG rearrangement, which precedes PTEN deletion in most cases, may directly or indirectly predispose tumor cells to PTEN loss.…”
Section: Discussionmentioning
confidence: 99%